26. GENETIC CHARACTERIZATION OF SELLAR METASTASIS FROM PRIMARY BRONCHIAL CARCINOID TUMOR OF NEUROENDOCRINE PATHOLOGY. (4th August 2020) - Hong, Christopher; McGuone, Declan; Erson-Omay, E Zeynep; Bulent Omay, Sacit
Abstract: Metastasis to the pituitary gland and surrounding sellar region from systemic tumors is a rare occurrence. Patients may present with signs of endocrine dysfunction secondary to pituitary involvement, as well as mass effect-related symptoms including headaches and visual deficits. Despite a small but accumulating body of literature describing the clinical and histopathological correlates for sellar metastases from systemic tumors, the genetic alterations underlying sellar spread have not been previously described. We describe a 68 year-old female with history of a resected lung carcinoid tumor, followed by chemoradiation, who was diagnosed with a sellar lesion on surveillance PET-CT and subsequent brain MRI. Her tumor was resected via an endoscopic endonasal approach, and final pathology was consistent with neuroendocrine origin, including positive immunohistochemistry for synpatophysin, CK7, TTF-1, and CAM5.2 with a Ki-67 index of 8–12%. Whole-exome sequencing of the sellar specimen demonstrated large-scale deletions of chromosomes 3, 6, and 9 and focal deletions on chromosomes 1, 2, 11, 15, and 16. Mutational signature analysis was enriched for COSMIC Signature 4, seen in multiple primary lung cancers. Among 91 total somatic alterations, 7 had been previously associated with oncogenesis ( MYO18A, PTCH1, BCOR, CLIC6, TLL2, COL1A1, PTPRK ). Notably, mutations in BCOR and PTCH1 have been previously implicated in both systemic neuroendocrine tumors as well as primary tumors of the pituitary gland, while MYO18A, FGF4, and PTPRK mutations had not been reported in systemic neuroendocrine tumors but have been implicated in tumor migration and pituitary adenoma progression. In summary, these data demonstrated an expected mutational pattern indicating a systemic lung neuroendocrine origin but also revealed new mutations previously implicated in primary pituitary pathologies that may have evolutionarily drove divergence from the primary tumor. Further genome studies of these rare lesions may yield further insight into the genetic alterations underlying metastasis to the sellar region.